2021
DOI: 10.3390/ijms222413589
|View full text |Cite
|
Sign up to set email alerts
|

Three Component Composite Scaffolds Based on PCL, Hydroxyapatite, and L-Lysine Obtained in TIPS-SL: Bioactive Material for Bone Tissue Engineering

Abstract: In this research, we describe the properties of three-component composite foam scaffolds based on poly(ε-caprolactone) (PCL) as a matrix and hydroxyapatite whiskers (HAP) and L-Lysine as fillers (PCL/HAP/Lys with wt% ratio 50/48/2). The scaffolds were prepared using a thermally induced phase separation technique supported by salt leaching (TIPS-SL). All materials were precisely characterized: porosity, density, water uptake, wettability, DSC, and TGA measurements and compression tests were carried out. The mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…The results are in good agreement with previously reported studies [51][52][53] regarding the biological properties of materials based on zinc ions and hydroxyapatite on human osteoblast cells MG-63 [50], mesenchymal stem cells derived from human adipose (MSCs) [44], and MRC-5 fibroblast cells [45]. More than that, in their study, Thian et al [44] reported that the presence of zinc ions in the structure of hydroxyapatite influenced the bioactivity properties of HAp.…”
Section: Resultssupporting
confidence: 90%
“…The results are in good agreement with previously reported studies [51][52][53] regarding the biological properties of materials based on zinc ions and hydroxyapatite on human osteoblast cells MG-63 [50], mesenchymal stem cells derived from human adipose (MSCs) [44], and MRC-5 fibroblast cells [45]. More than that, in their study, Thian et al [44] reported that the presence of zinc ions in the structure of hydroxyapatite influenced the bioactivity properties of HAp.…”
Section: Resultssupporting
confidence: 90%
“…In recentyears, due to the increase in pathological conditions of bones, tissue engineering and regenerative medicine were highly employed in the treatment of these conditions [44][45][46][47][48][49][50]. For this purpose, over the years, extensive studies were undergone regarding the employment of biocompatible and bioresorbable materials with enhanced biological properties and having controllable degradation and resorption properties in the development of new devices for bone treatment [45,48].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the concentrations of OC and IL-6 in the culture media of hFOB 1.19 were determined by enzymelinked immunosorbent assay (ELISA, R&D Systems, Minneapolis, MN, USA) according to the manufacturer's instructions. The sensitivity of ELISA test for OC and IL-6 was 156.5 pg/mL and 9.38 pg/mL, respectively [32].…”
Section: Osteoconductive Potentialmentioning
confidence: 96%
“…To assess the hFOB 1.19 osteoconductive potential, osteoblasts were grown in the milieu of a particular nanoHAP under osteoinductive conditions (39°C; differentiation medium: DMEM F-12 without phenol red, with 1% bovine serum, containing G148 geneticin and stimulants: β-glycerophosphate, ascorbic acid, dexamethasone, and the addition of the tested samples at a concentration of 5 mg/mL). As previously described, at the de ned time points (7, 14, 21, and 28 days), the activity of alkaline phosphatase (ALP), cell proliferation, and the release of osteocalcin (OC) and interleukin-6 (IL-6) were quanti ed [31,32]. Brie y, cell proliferation was evaluated based on DNA quanti cation by CyQuant® assay (Thermo Fisher Scienti c).…”
Section: Osteoconductive Potentialmentioning
confidence: 99%